A centralized multi-objective model predictive control for a biventricular assist device: An in vitro evaluation. (May 2020) - Koh, V.C.A.; Pauls, J.P.; Wu, E.L.; Stevens, M.C.; Ho, Y.K.; Lovell, N.H.; Lim, E.
Highlights: The proposed controller is superior than the constant speed setting. The proposed controller increased exercise capacity by increasing flow rate. The proposed controller avoided ventricular suction in extreme scenarios. The proposed controller avoided vascular congestion in extreme scenarios. Abstract: Control of a biventricular assist device (BiVAD) is more challenging than control of a left ventricular assist device due to the process interactions between control loops in a multi-input-multi-output system. Hence, a single centralized multi-objective model predictive controller (CMO-MPC) has been developed to control a BiVAD. The CMO-MPC aims to: 1) adapt pump flow rate according to the Frank-Starling mechanism, 2) avoid ventricular suction, and 3) avoid vascular congestion. The CMO-MPC was benchmarked against a constant-speed (CS) setting in exercise, postural change, and systemic vascular resistance change tests in a mock circulation loop. The CMO-MPC increased pump flow rate from 5.0 L/min to 7.6 L/min in the exercise scenario, which was higher than the pump flow rate in the CS setting (6.0 L/min). In the postural change test, right ventricular end diastolic pressure (RVEDP) decreased to a minimum at 0.1 mmHg and 2.0 mmHg in the CS setting and the CMO-MPC, respectively, indicating that the CMO-MPC could minimize the risk of ventricular suction (with higher minimum RVEDP than the CS setting) when there was a sudden decrease in venous return. In all tests, the CMO-MPC could adapt pump flow rate without resulting events of ventricular suction and vascular congestion.